Safety evaluation of the food enzyme chymotrypsin from the genetically modified Bacillus licheniformis strain NZYM‐RH - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme chymotrypsin (EC 3.4.21.1) is produced with the genetically modified microorganism Bacillus licheniformis strain NZYM‐RH by Novozymes A/S. The genetic modifications do not give rise to safety concerns. The production strain met the requirements for the qualified presumption of safety (QPS) approach. The food enzyme is considered free from viable cells of the production organism and its DNA. The food enzyme is intended to be used in six food manufacturing processes. Dietary exposure was estimated to be up to 1.945 mg TOS/kg body weight (bw) per day in European populations. Given the QPS status of the production strain and the absence of concerns resulting from the food enzyme manufacturing process, the toxicological studies provided were considered not necessary according to the current guidance but evaluated as supportive evidence. A search for the homology of the amino acid sequence of the chymotrypsin to known allergens was made and no match was found. The Panel considered that a risk of allergic reactions upon dietary exposure to the food enzyme cannot be excluded, but that the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.